Database Management Education in MYSQL - Jodi Wahyudi; Masduki Asbari; Ipang Sasono; Tias Pramono; Dewiana Novitasari (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this research is to find out what is database management in MySQL or read My Sequel is a Database Management System often abbreviated as DBMS, MySQL is an open-source database management system. MySQL can be used to create and manage databases and their contents, from the smallest to the very large and to convey information to its users. MySQL is also included in the RDBMS or Relational Database Management system, where in its database structure so that when the data retrieval process uses the relational database method and becomes a liaison between the software and the database server. The thing to remember is that MySQL can be used for free.